Correlations of Photoluminescence and Size Evolution of Si Quantum Dots in Amorphous Silicon Carbide. Issue 12 (December 2015) - Gengrong, Chang; Fei, Ma; Fuxing, Fu; Kewei, Xu
Abstract: Silicon quantum dots (Si QDs) with dot density up to 9×10 13 cm −2 in amorphous Si x C (x>1) thin films were obtained by magnetron sputtering deposition and post-annealing process at 1100 °C. Photoluminescence measurement indicates a multi-band configuration in the range from ultraviolet to green (2.3∼3.5 eV). The analysis of Stokes shift and HRTEM demonstrates that there exist two kinds of Si QDs embedded in silicon carbide dielectric matrix: α -Si QDs and c-Si QDs which show the multi-band characteristics. The photoluminescence is closely related with the microstructure size distribution of Si QDs from 1.0 to 4.0 nm. Moreover, the density and the size distribution of Si QDs can be improved further by optimizing the ratio of Si/C atoms as well as annealing parameters. This opens a route to fabricate all-Si tandem solar cell.